Exploring TESL pre-service teachers’ knowledge to integrate critical thinking in their teaching - Mansor, Majdina; Khalid, Madihah (Centre for the Advancement of Language Competence (CALC), Universiti Putra Malaysia, 2024)
The current study investigated TESL pre- service teachers’ knowledge about critical thinking and how to integrate it in their teaching. In addition, the study also explored the influence of ‘year of study’ towards TESL pre-service teachers’ perceived level of knowledge. The study was conducted with a total of 106 TESL students from a Malaysian public university. A questionnaire that measures knowledge on a 5-point Likert scale was used in the survey. The data were analysed quantitatively using descriptive statistics and One-Way ANOVA. The results showed that TESL pre-service teachers’ knowledge to integrate critical thinking in their teaching is high. Nevertheless, it was revealed that although not significant, TESL pre-service teachers’ level of knowledge was slightly influenced by ‘year of study’. This finding shows that there are certain areas of teacher training that could be enhanced to ensure the integration of critical thinking in instruction is well on its way to achieve the objectives stated in the Malaysian Education Blueprint.